Analysis of failure rates among calcium hydroxide, biodentine, and mineral trioxide aggregate in direct pulp capping procedures: a systematic review - Tifani, Amara Syifa; Nugraeni, Yuli; Rachmawati, Ranny; Huang, Haw-Ming; Fauzi, Adam (Universitas Padjadjaran, 2026)
Introduction: Direct pulp capping is a conservative treatment approach aimed at preserving pulp vitality following pulp exposure. Calcium hydroxide (Ca(OH)₂), mineral trioxide aggregate (MTA), and Biodentine are commonly used materials for this procedure. This systematic review aimed to compare the clinical, radiographic, and histological outcomes associated with these materials in direct pulp capping procedures. Method: A systematic literature search was conducted in PubMed, Scopus, ScienceDirect, and Google Scholar for studies published between 2015 and 2025. Only in vivo human clinical studies involving permanent teeth treated with Ca(OH)₂, MTA, or Biodentine were included. Study selection followed PRISMA guidelines. Data extraction focused on clinical success, pulp vitality, dentin bridge formation, and follow-up outcomes. Due to heterogeneity among the included studies, results were synthesized narratively. Results: Six clinical studies met the inclusion criteria and were included in the qualitative synthesis. Reported success rates for Ca(OH)₂ ranged from 13% to 37% in long-term follow-up. MTA demonstrated success rates exceeding 80% in studies with follow-up durations of at least 12 months. Biodentine showed comparable or slightly higher success rates than MTA in short- to medium-term observations. Radiographic and histological outcomes indicated more continuous dentin bridge formation in the MTA and Biodentine groups compared to Ca(OH)₂. Conclusion: Based on the available evidence, calcium silicate–based materials such as MTA and Biodentine appear to provide more favorable clinical and biological outcomes than calcium hydroxide for direct pulp capping procedures. Material selection should consider both biological performance and clinical handling characteristics to optimize treatment outcomes.